A public health approach for preventing neural tube defects: folic acid fortification and beyond. Issue 1 (16th February 2018) - Garrett, Greg S.; Bailey, Lynn B.
Abstract: In this paper we review the evidence basis for prevention of folic acid–sensitive neural tube defects (NTDs) through public health interventions in women of reproductive age (WRA), the proven vehicles for delivery of folic acid, and what is needed to effectively scale these, and provide a snapshot of potential innovations that require future research. Our primary focus is on the global situation affecting large‐scale food fortification (LSFF) with folic acid, in particular the fortification of wheat flour and maize meal. Our overarching conclusion is that folic acid fortification is an evidence‐based intervention that reduces the prevalence of NTDs, and that LSFF with folic acid is underutilized. Thus, food fortification with folic acid should be a component of most national public health strategies, in particular where folate status is insufficient and a fortifiable food vehicle, processed by a centralized industry, is consumed regularly by WRA. The evidence shows that there is still much work needed (1) to build the enabling environment and expand programs where there is currently no legislation, (2) to improve the low quality of delivery of existing programs, and (3) to measure and sustain programs by generating new coverage data and demonstrating evidence of impact in low‐ and middle‐income countries.